Encyclopedia of food microbiology - Robinson, R. K. (Richard Kenneth); Batt, Carl A.; Patel, P. D. (Pradip D.) (Academic Press, 2000)
The Encyclopedia of Food Microbiology, Three-Volume Set is the largest comprehensive reference source of current knowledge available in the field of food microbiology. Consisting of nearly 400 articles, in three volumes, written by the world's leading scientists, the Encyclopedia presents a highly structured distillation of the whole field--from Acetobacter to Zymomonas. Each article in the Encyclopedia is approximately 4000 words in length and contains tables, line drawings, black-and-white photographs, or electron micrographs, where appropriate. The articles critically review the current state of knowledge of the topic in question. A list of suggested further reading is provided at the end of each article allowing the interested reader to research the subject more closely.The Encyclopedia is written at the research/technician level and could be used as a coursebook. Practitioners in industry, analysts, and similar professionals will especially be interested in the methodologies and techniques theme. Includes 358 articles in the following areas of Food Microbiology:* Food-borne organisms: their characteristics and importance* Micro-organisms in action* Detection and enumerationKey Features:* Provides an alphabetical article listing and a listing arranged according to subject area* Offers further reading lists in each article which allows easy access to the primary literature* Contains extensive cross-referencing and complete subject index in each volume* Includes many figures and tables illustrating the text and color plate sections in each volumeArticles cover:* All the major genera/groups of food spoilage and food-borne disease organisms* The beneficial activities of bacteria and fungi in the food industry* Industrial aspects of microbiology* The microbiology of specific commodities* Classical methods for the enumeration of bacteria and fungi* Total colony counts for the detection and/or enumeration of specific genera/species* MPN procedures, dye reduction tests, and direct microscopic counts* Recent methods for examining foods, e.g. automated PCR and ELISAs * Current tests for individual genera such as API carbohydrate strips